Air Induction System Check on Toyota Soluna Engineer Stand - Bintha Ustafiano; Supriadi Supriadi; Fajar Maulana (VANOS Journal of Mechanical Engineering Education, 2023)
The purpose of this study is to examine the Air Induction System on the Toyota Soluna 5A-FE Engine Stand. The research method used an experimental method and was carried out for two months from July 2020 to August 2020 at the Padang State University Workshop.How to check the components of the Toyota Soluna 5A-FE engine stand air induction system is divided into three ways, namely, voltage check, resistance check, and visual inspection. The purpose of examining the air induction system on the Toyota Soluna 5a-fe engine stand is to repair the Toyota Soluna engine stand in the FT UNP automotive workshop so that it can be reused as material for the teaching and learning process in the FT UNP automotive workshop. The Toyota Soluna 5a-fe engine stand in the FT UNP automotive workshop is in a dead engine condition, the wiring system is messy and some parts of the stand are porous. Therefore, the author will examine the air induction system on the Toyota Soluna 5a-fe engine stand. The inspection process for the Toyota Soluna 5a-fe engine stand air induction system consists of: the process of dismantling the components of the air induction system, the process of checking the components of the air induction system, the process of repairing the wiring system, the process of installing components after the inspection process is complete, the testing process is carried out and the Toyota Soluna engine stand can live normally so that it can be reused as teaching material in the FT UNP automotive workshop.